Transcriptional and functional characterization of terpene synthase genes of the aromatic plant Plectranthus hadiensis - Hinano Mizuno; Kenro Tokuhiro; Koichiro Iwai; Yoshikazu Furuta; Akari Nakasone; Hidenori Tanaka; Hiroki Sugimoto (PLoS ONE, 2026)
Plectranthus hadiensis (Lamiaceae) is recognized for its rich terpene content and potential applications in agriculture, medicine, and aromatherapy. Terpenes are major constituents of P. hadiensis essential oil, yet its terpene synthase (TPS) genes remain insufficiently characterized. In this study, we assembled a de novo transcriptome from RNA-seq data generated from leaf, stem, and root tissues and identified 26 TPS genes. Phylogenetic analysis classifies these genes into five TPS subfamilies (TPS-a, TPS-b, TPS-c, TPS-e/f, and TPS-g), broadly associated with sesquiterpene, monoterpene, and diterpene biosynthesis. Expression profiling revealed apparent tissue specificity; notably, PhTPS1 showed high transcript abundance in the leaf and stem. BLASTP analysis indicated that PhTPS1 is closely related to Lamiaceae monoterpene synthases, with the top hit being a rosemary ( Salvia rosmarinus ) limonene synthase. Heterologous expression of PhTPS1 in yeast, followed by headspace gas chromatography-mass spectrometry, detected limonene, confirming PhTPS1 as a functional limonene synthase. To our knowledge, this is the first limonene synthase gene functionally characterized in P. hadiensis . Collectively, these findings provide a curated TPS genes catalog with their tissue-specific expression patterns and identify PhTPS1 as a promising target for breeding and metabolic engineering to enhance limonene yield.